Nanoantibiotics: Functions and Properties at the Nanoscale to Combat Antibiotic Resistance - Mamun, M. Mustafa; Sorinolu, Adeola Julian; Munir, Mariya; Vejerano, Eric P. (Frontiers in Chemistry, 2021)
Antibiotics in their free or bulk molecular form suffer drug resistance due to bacteria developing resistance mechanisms that render most antibiotics ineffective. Nanoantibiotics are antibiotic molecules encapsulated with engineered nanoparticles (NPs) or artificially synthesized pure antibiotics in a size range of ≤ 100 nanometers (nm) in at least one dimension. Nanoantibiotics may restore drug efficacy using carriers and delivery agents of drug molecules, thus reaching target sites by crossing the bacterial membranes, and ultimately, internalized by cellular components. Nanoscale systems deliver antibiotics at enormous nanoparticle number concentrations. Their unique size-, shape-, and composition-related properties pose multiple simultaneous antibacterial mechanisms. Due to the availability of diverse types and various targets of nano-based antibiotics, the scope of developing further bacterial resistance towards these nanoscale drug conjugates is considerably slower. This review discusses how to exploit the potential of nanoantibiotics using their fundamental physical and chemical properties to restore the efficacy of conventional antibiotics that modulate biological activities inside bacteria. In this review, we first described the concept of nanoantibiotics. Next, we explained the importance of nanoantibiotics. Finally, we summarized the fundamental physical and chemical aspects of nanoantibiotics and their types that one should utilize in the manufacture and design of restoring antibiotic efficacy. The mechanistic insights from this review on a potential strategy to circumvent antibacterial resistance mechanisms exposed to nanoengineered systems will provide understanding into host cell-bacterium-antibiotic interactions.